Comparative effectiveness of hand and ultrasonic instrumentations in root surface planing in vitro - Khosravi, Mahmood; Bahrami, Zahra Samadi; Atabaki, Mahdi Saheb Jam; Shokrgozar, Mohammad Ali; Shokri, Fazel (Journal of clinical periodontology, 2004)
Background/aims: A variety of techniques are employed for planing and scaling of the superficial root surfaces, of which hand and ultrasonic instrumentations have been preferentially used in routine periodontics clinics. This study was undertaken to compare the effectiveness of ultrasonic scalers and hand curettes in facilitating fibroblast attachment to the scaled root surfaces. Materials and Methods: Sixteen patients with periodontally involved teeth and nine subjects without periodontal diseases (control subjects) were selected. Two single‐rooted teeth were extracted from each subject. Mesial and distal surfaces of teeth were selected in treated and untreated groups, respectively. The mesial surface of each tooth was randomly chosen to be treated either by hand curettes or ultrasonic instrumentation. The degree of cell attachment on the root surfaces of treated and untreated groups from control subjects and patients was then determined by the use of a gingival fibroblast line established and employed at early passages. The attachment and proliferation of gingival fibroblasts on the root surfaces were evaluated using neutral red assay and scanning electron microscopy (SEM). Results: Fibroblast survival and proliferation on the surfaces of untreated periodontally involved roots were found to be significantly lower compared with control untreated surfaces (p<0.0001) or treated surfaces from patients (p<0.0001). No significant difference, however, was observed between root surfaces treated either by hand curettes or ultrasonic scalers. Conclusion: These results indicate the beneficial effectiveness of both techniques in root treatment and planing.